Pengaruh Proporsi Santan dan Susu Kedelai dalam Pembuatan Keju Oles Analog - Prabowo, Ivy (Universitas Ahmad Dahlan, 2024)
The basic ingredient for making spreadable cheese is cow's milk. However, some people are unable to consume cow's milk because of lactose intolerance or preference for vegan lifestyle. Vegetable milks, such as coconut milk and soy milk, offer alternatives for producing analog cheese that can be consumed by a wider range of individuals. This research aims to analyze the composition of coconut milk and soy milk to produce an analog cheese that is acceptable to consumers based on orgnoleptic properties, including taste, aroma and texture. This study utilized a Completely Randomized Design (CRD) method, testing five different formulations with varying proportions of coconut milk and soy milk. In this research, the best formula was identified through an organoleptic test, where participant rated the cheese on a scale of 1 to 5 (1=very dislike, 5= very like). Datawere analyzed descriptively quantitatively using a t-test with a significance level of 0.05. The result indicated that the proportion of coconut milk and soymilk significantly affected the organoleptic properties of texture and aroma, but not the taste. Panelists preferred spreadable cheese with 100% coconut milk, which received a taste score of 3.97, an aroma score 4.57, and a texture score of 4.00. The analog cheese made from 100% coconut milk contained 8,55% protein and 10,02% fat.